Algorithmic game theory : 8th International Symposium, SAGT 2015, Saarbrücken, Germany, September 28-30, 2015, Proceedings /: 8th International Symposium, SAGT 2015, Saarbrücken, Germany, September 28-30, 2015, Proceedings. (2015) - Unknown
No abstract available